Personal reflection training model for teenage martial arts - Kolodeznikova, M. G.; Cherkashin, Z. N.; Mikhailova, T. A. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to analyze the teenage personal reflection formation logics and offer new personal reflection training model for teenage martial arts.